Design a smoke filter control system in fish burning furnaces to reduce the impact of air pollution - Raafi'u, Brian; Syaifunnuwas, Tyjani Robit (Faculty of Vocational Studies - Research Center, DRPM ITS, 2024)
Smoke filter technology using electrostatic preciptitator (ESP) is one of the methods of reducing smoke using copper slabs supplied with high voltage DC electricity. Voltage input comes from PLN 220 AC and converted into DC voltage and raised using flyback converter. When smoke passes through a negatively charged copper plate there will be irradiation and when it passes through a positively charged copper plate the smoke particles will be reduced. Used 2 carbon monoxide gas sensors to determine the success of the smoke filter system using electrostatic preciptitator, the system succeeds if the second sensor reading value is not more than 101 ppm (part per million) according to those determined by the local government so that it is safe for the environment. The quality of exhaust carbon monoxide (CO) gas emissions from the processing of this plant is better at about 31.46 ppm than 615.92 ppm (part per million) and can reduce the impact of air pollution produced by home industry despite the use of copper plates supplied by high voltages. Dust particles contained in smoke are able to filter about 0.18gram within 330 minutes. The reading results will be displayed on blynk as a form of monitoring.